Reduced ectoparasite loads of deer mice in burned forest: From fleas to trees?. Issue 10 (31st October 2013) - Zwolak, R.; Meagher, S.; Vaughn, J. W.; Dziemian, S.; Crone, E. E.
Abstract : We tested whether reduced parasite loads might contribute to high post‐fire abundances of deer mice ( Peromyscus maniculatus ). We performed parasite examinations of 54 mice captured in burned forest in the area of Davis Fire (western Montana, USA), and 26 mice captured in nearby unburned forest. Mean abundance of ectoparasites (fleas, ticks, and lice) was lower in burned than in unburned forest. The difference was particularly pronounced for fleas, which were reduced by 70% in burned forest. Endoparasites (i.e., nematodes and cestodes) were unaffected. Mechanisms for the lower mean abundance of fleas in burned areas are not known, but might involve flea mortality in burrows during fire or decreased transmission, survival, or both in the post‐fire environment. We propose several hypothetical pathways through which reduced ectoparasite loads could cause an increase in deer mouse abundance, such as improved health status or increased foraging efficiency of mice, both of which could translate into the increased reproduction that has been reported in mice from burned forest. We encourage experimental tests of the ectoparasite release hypothesis of the post‐fire increase in deer mouse abundance.